Marketing for nonprofit organisations - Wymer, Walter (Henry Stewart Talks, 2012)
Dimensions of nonprofit marketing, Importance of the nonprofit sector, Nonprofit brands, Nonprofit positioning & communication, Resource attraction, Division of services, Categorisation & types of nonprofit organisations, Challenges faced by the nonprofit sector, Adoption of marketing approach, Marketing planning for nonprofit organisations, Strategic objective and marketing goals, Guidelines for creating a marketing plan, Marketing program budget, Fundraising areas, Examples of marketing activities
Archived at 2022/04/26